THE EFFECT OF USING WORD PRICK CARDS ON LEARNING OUTCOMES AT FIE SABILIL MUTTAQIEN PARON MIDDLE SCHOOL, NGAWI, EAST JAVA - Budiman, Agus; Nafisah, Mafazatun; Azizah, Aprilya; Austi, Zhilaluha (Abjadia : International Journal of Education, 2024)
This study aims to determine the differences in learning outcomes between control class students and experimental class students, as well as the effectiveness of using word punch card learning media in Arabic language learning for grade 7 students at MTs Fie Sabilil Muttaqien, Paron, Ngawi. Currently, Arabic language teaching at this madrasah only uses the lecture method without learning media, which causes a decline in student learning outcomes. This research employs a quantitative experimental method with a Quasi-Experimental Design and hypothesizes that word punch card media is effective for learning outcomes. Data were collected through tests, interviews, observations, and documentation, and analyzed using the Mann-Whitney formula. The results show significant differences in learning outcomes between the experimental and control classes. The average learning outcome for the experimental class was 8.88, while the control class was 8.25. The Mann-Whitney test indicated an asymp.sig (2-tailed) value of 0.034 > 0.05, thus the alternative hypothesis is accepted.